2016
DOI: 10.1558/cj.v33i1.29251
|View full text |Cite
|
Sign up to set email alerts
|

Automated Writing Evaluation in Language Teaching: Theory, Development, and Application

Abstract: The first automated writing evaluation (AWE) software for assessment purposes dates back to the 1960s when Page Ellis developed Project Essay Grade (PEG). Rapid advances in the fields of artificial intelligence and Natural Language Processing (NLP) in the last few decades have led to the development of more powerful commercial scoring engines, such as e-rater, developed by ETS, IntelliMetric by Vantage Learning, and Intelligent Essay Assessor (IEA) by Pearson Education. Recent years have seen the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Secondly, this study examined the students' perception on the use of Grammarly and teacher feedback to know whether the students take the benefits of the combination or not. The studies which focused on the effectiveness of AWE recomended researchers to find out more about the students' perspective on the implementation of different AWE programs Cotos (2011); Hegelheimer et al (2015). Lastly, this study, which uses Grammarly and teacher feedback at both high and low language proficiency levels, also investigates whether the two feedback strategies benefit particular students based on the language level.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, this study examined the students' perception on the use of Grammarly and teacher feedback to know whether the students take the benefits of the combination or not. The studies which focused on the effectiveness of AWE recomended researchers to find out more about the students' perspective on the implementation of different AWE programs Cotos (2011); Hegelheimer et al (2015). Lastly, this study, which uses Grammarly and teacher feedback at both high and low language proficiency levels, also investigates whether the two feedback strategies benefit particular students based on the language level.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is suggested to perform the AWE in non-English major students (Yinghui & Dan, 2015). It has also been suggested to find out how the implementation of a different AWE program is perceived by the students (Hegelheimer et al, 2016). Certainly, the interface of different AWE programs can be one factor that determines its impact to the students.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the students' view is essential to find out whether the students valued the use of an AWE program or not. As there are many studies focus on the effectiveness of AWE, it was suggested to find out more about the potential and students' view on the implementation of different AWE programs (Cotos, 2011;Hegelheimer et al, 2015). Most studies about AWE also largely conducted in the English language major classes.…”
Section: Figure 1 Prowritingaid Editing Pagementioning
confidence: 99%
“…4, No. 10, Bln Oktober, Thn 2019, Hal 1353-1363 (AWE) is software that can give automatic feedback to the students' writings (Hegelheimer, Dursun, & Li, 2015). Unlike the teacher or peer feedback that needs more time in generating feedback, AWE can give feedback instantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation